Implementation evaluation of an Irish secondary-level whole school programme: a qualitative inquiry. (26th October 2022) - McHale, Fiona; Ng, Kwok; Scanlon, Dylan; Cooper, Jemima; Grady, Caera; Norton, Catherine; O'Shea, Donal; Woods, Catherine
Summary: Whole-of-school programmes (WSPs) are recommended to promote physical activity for adolescents. The Active School Flag (ASF) programme for secondary-level schools is one such WSP. Due to the difficulties of incorporating WSPs into the complex school system, there is a risk of poor implementation. The monitoring of unanticipated influences can help to understand key implementation processes prior to scale-up. The aims of this study were to identify perceived facilitators and barriers to implementing the ASF and recommend evidence-based implementation strategies. Focus groups and interviews ( N = 50) were conducted in three schools with stakeholders involved in programme implementation, i.e. school management ( n = 5), ASF coordinator ( n = 4), student-leaders (aged 15–16 years) ( n = 64) and staff committee ( n = 25). Transcripts were analysed using codebook thematic analysis and were guided by the Consolidated Framework for Implementation Research. Implementation strategies were identified and were selected systematically to address contextual needs. Three themes surrounding the facilitators and barriers to implementation were generated: intervention design factors (e.g. capacity building and knowledge of implementers; and interest and buy-in for the programme), organizational factors (e.g. optimization of people and the busy school environment) and interpersonal factors (e.g. communication and collaboration). The examination of facilitators and barriers to implementation of the ASF has assisted with the identification of implementation strategies including (not limited to) a shared leadership programme for student leaders and a more flexible timeline for completion. These facilitative implementation strategies may assist in the effective implementation of the ASF. Lay Summary: A large proportion of adolescents do not meet the current physical activity (PA) recommendations. Whole school programmes (WSPs) are recommended for the promotion of PA. However, secondary-level schools are a busy and complex setting, thus leading to challenges in making such WSPs work. The Active School Flag (ASF) programme for the secondary level is one such WSP that aims to increase PA opportunities in schools and local communities. The identification of facilitators and barriers to carrying out or implementing programmes can help researchers identify ways to solve the barriers to uptake and also leverage the facilitators. Researchers conducted interviews and focus groups with all the stakeholders involved in the implementation of the ASF. The analysis revealed three themes revealing both facilitators and barriers surrounding the following: (i) intervention design factors, (ii) organizational factors and (iii) interpersonal factors influencing implementation. This analysis assisted researchers in identifying ways to support the implementation of the ASF through the recommendation of implementation support strategies, e.g. the development of a shared leadership programme for student leaders and the development of a more flexible timeline for the completion of the ASF programme. These strategies may assist in the improved implementation of the programme and thus greater success in the achievement of programme outcomes.